Strict Solution for a Second Order Differential Equation in Holder Spaces - Youcef Naas; Fatima Zohra Mezeghrani (International Journal of Analysis and Applications, 2019)
In this paper we give some results on abstract second order differential elliptic equations of mixed type. The study is performed in Holder continuous Banach spaces. Our main purpose is the study of necessary and sufficient conditions on the data for obtaining existence, uniqueness and maximal regularity properties of the strict solution. The techniques used are based on analytic semigroups theory.